Methods for estimating the soybean potential yield during ontogeny - Pires, João Leonardo Fernandes; Costa, José Antonio; Rambo, Lisandro; Ferreira, Felipe Gutheil (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to study methods to estimate the soybean potential yield during ontogeny. The experiments were performed in Eldorado do Sul, RS, during the growing seasons of 1996/1997, 1999/2000 and 2000/2001. The treatments consisted of five soybean cultivars, FT-Saray, IAS 5, IAS 4, FT-Abyara and FEPAGRO RS-10. It was calculated the potential yield of each cultivar, by five methods, in order to estimate the yield that would be obtained if all the reproductive structures during flowering and beginning of pod filling produced grains at the maturity. Potential yield (during flowering and pod filling) presented a high correlation with the number of flowers and reproductive structures, respectively. It was also found a correspondence among the methods. Most of the time, it did not occurred significant correlations between potential (during flowering and pod filling) and the grain yield in maturity. The studied methods are important tools for the management of soybean crops, used to compare the potential yield during ontogeny.